Formulation and Evaluation of Ketoprofen Gel Preparations, Sesami Oil Soybean Oil and Oleic Acid as Enhancers - Rugun Clara Samosir; Iyan Sopyan; Dolih Gozali (Universitas Padjadjaran (Unpad), 2019)
Permeation is a measurable profile in drug penetration in skin. Adding increasing permeation substance (enhancer) in drug formulation is an important thing in pharmaceutical and toxicology in nowadays. The purpose of this research was to evaluate the effect of sesame oil, soybean oil, and oleic acid as enhancer in ketoprofen gel permeation. Six formula were prepared by varying concentration of sesame oil, soybean oil, and oleic acid respectively 5% and 10% and one blank, without enhancer. Permeation test was evaluated by in vitro permeation test using Franz diffusion cell method and shed snake skin of reticulated python as a membrane. Permeation test were carried out for 6 hours. The result showed that sesame oil, soybean oil, and oleic acid were able to increase ketoprofen permeation. B1 formula that contain 5% sesame oil had greatest percent permeation after 6 hours is 5.913%, while blank that contain no enhancer is 0.623%.Keywords: ketoprofen, permeation, enhancer, soybean oil, sesame oil, oleic acid.